2004
DOI: 10.1002/sia.1833
|View full text |Cite
|
Sign up to set email alerts
|

Optical and mechanical properties of polypropylene modified by metal oxides

Abstract: Films of polypropylene (PP)/SiO 2 , PP/ZnO and PP/SiO 2 -ZnO nanocomposites have been prepared. SiO 2 and ZnO were prepared by the sol-gel method and mixed with dispersant (Efka) and coupling agent (thiocyanatopropyltriethoxysilane) before being introduced to melted PP in an internal mixer. The transmission of UV, visible light and NIR radiation of the nanocomposite films was less than that of the PP films. Efka and silane made the film clearer to all rays since they hindered the particle agglomeration. PP/ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Increasing RH particle loading resulted in an abrupt drop in elongation at break for PP/RH/TiO2 and PP/RH/ZnO as compared to neat PP in (Figure 3). Generally, an incorporation of inorganic fillers into polymer composites enhances their mechanical properties such as tensile strength, elastic modulus but decreases impact strength and elongation at break [18,26,27]. Based on Figure 3, it also can be observed that elongation at break for PP/RH/TiO2 was higher than PP/RH/ZnO.…”
Section: Thermogravimetric Analysismentioning
confidence: 68%
“…Increasing RH particle loading resulted in an abrupt drop in elongation at break for PP/RH/TiO2 and PP/RH/ZnO as compared to neat PP in (Figure 3). Generally, an incorporation of inorganic fillers into polymer composites enhances their mechanical properties such as tensile strength, elastic modulus but decreases impact strength and elongation at break [18,26,27]. Based on Figure 3, it also can be observed that elongation at break for PP/RH/TiO2 was higher than PP/RH/ZnO.…”
Section: Thermogravimetric Analysismentioning
confidence: 68%
“…Zinc oxide nanoparticles were used as reinforcement fillers for improving the structural properties of a wide range of polymers such as rubber [159], PP [160], PET [161], epoxy resin [162,163], PMMA [164], polysulfone [165] and many others [166][167][168][169][170]. Also nanocomposites based on renewable sources were studied [171].…”
Section: Structural Applicationmentioning
confidence: 99%
“…Commercial thermoplastics such as polyethylene, polypropylene (PP), polyvinyl chloride, and polystyrene are commonly used in the manufacture of plastic/wood fi ber composites (Sobczak et al, 2013;Bledzki and Gassan, 1999;Rowell et al, 1997;Oksman and Sain, 2008). Polymers are used in many areas, such as automotive, electronics, and different construction equipment (Aydemir et al, 2016;Kruenate et al, 2004). The use of technical and standard plastics has encouraged the application of natural fi bers thanks to their low prices and steadily rising performance (Witting, 1994;Zor et al, 2016).…”
Section: Uvodmentioning
confidence: 99%